Cutaneous Vasculitis: An Unusual Presentation of a Biclonal Nodal Plasma Cell Dyscrasia - D. Swan; M. Murphy; E. Elhassadi (Case Reports in Hematology)
We describe an unusual case of a biclonal nodal plasma cell dyscrasia, presenting with a vasculitic rash, end-organ damage, and cytopenias. Serum protein electrophoresis demonstrated a biclonal kappa-restricted paraprotein, with a negative skeletal survey and no bone marrow disease. Fluorodeoxyglucose-PET-CT (FDG-PET-CT) revealed nodal involvement, which was not appreciable clinically, and facilitated biopsy, confirming the diagnosis of a nodal plasmacytoma. Complete biochemical response and resolution of the vasculitic rash were achieved with bortezomib-based therapy.